The Innovative Medicines Initiative neurodegeneration portfolio: From individual projects to collaborative networks - O'Rourke, Diana; Coll-Padrós, Nina; Bradshaw, Angela; Killin, Lewis; Pradier, Laurent; Georges, Jean; Dawoud, Dalia M.; Steukers, Lennert; Diaz, Carlos (Frontiers in Neurology, 2022)
The IMI public-private partnership between the European Commission and the European Federation of Pharmaceutical Industries and Associations (EFPIA) was launched in 2008 with an initial budget of €2bn. Aiming to accelerate the development of innovative medicines for areas of unmet clinical need, the IMI has committed over €380 million to projects on neurodegenerative disorders (NDD), catalysing public-private collaborations at scale and at all stages of the R&D pipeline. Because of this vast investment, the field of neurodegenerative disease research has made enormous strides in recent decades. The challenge for the future however remains to utilise this newly found knowledge and generated assets to develop better tools and novel therapeutic strategies. Here, we report the results of an integrated programme analysis of the IMI NDD portfolio, performed by the Neuronet Coordination and Support Action. Neuronet was launched by the IMI in 2019 to boost synergies and collaboration between projects in the IMI NDD portfolio, to increase the impact and visibility of research, and to facilitate interactions with related initiatives worldwide. Our analysis assessed the characteristics, structure and assets of the project portfolio and identifies lessons from projects spanning preclinical research to applied clinical studies and beyond. Evaluation of project parameters and network analyses of project partners revealed a complex web of 236 partnering organisations, with EFPIA partners often acting as connecting nodes across projects, and with a great diversity of academic institutions. Organisations in the UK, Germany, France and the Netherlands were highly represented in the portfolio, which has a strong focus on clinical research in Alzheimer’s and Parkinson’s disease in particular. Based on surveys and unstructured interviews with NDD research leaders, we identified actions to enhance collaboration between project partners, by improving the structure and definition of in-kind contributions; reducing administrative burdens; and enhancing the exploitation of outcomes from research investments by EU taxpayers and EFPIA. These recommendations could help increase the efficiency and impact of future public-private partnerships on neurodegeneration.